Strategi Marketing Mix Jasa Pendidikan dalam Meningkatkan Minat Masyarakat - Sulistyaningrum, Anisa; Ainur Rifqi; Ima Widiyanah; Amrozi Khamidi; Mochamad Nursalim (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to identify the marketing strategies implemented by SDIT Al Uswah Surabaya in increasing public interest. Using a qualitative case study approach, this study explores in depth the key elements of the marketing mix implemented by the school. Data collection was carried out through observation, in-depth interviews with related parties, and document studies. Data analysis used the Creswell data analysis model, which includes data processing and preparation, reading all data, coding data, presenting descriptions or themes in qualitative narratives, and interpreting data. The results of the study indicate that SDIT Al Uswah Surabaya has succeeded in implementing an effective marketing strategy, which is reflected in the high public interest and the school's proud achievements. The superior Al-Qur'an memorization program, prices that are in accordance with the quality of service, strategic location, utilization of social media and direct promotional activities, competent teaching staff, clear school vision and mission, and adequate facilities and infrastructure are key factors in the success of the school's marketing strategy. This study provides insight into the importance of implementing a comprehensive marketing strategy in the context of educational institutions to increase competitiveness and attract public interest.   Keywords: Marketing Mix, Marketing Strategy, SDIT Al Uswah Surabaya